Afectación de Violencia Intrafamiliar, en Mujeres de 18 a 25 Años de la localidad Ciudad Bolívar, Bogotá (2021)
Violence is a phenomenon that has been presenting alarming figures in Colombia, especially where the victim is a woman. Therefore, this research proposed as a general objective to identify the psychological effects that domestic violence entails in women between 18 and 25 years old who live in the town of Ciudad Bolívar de Bogotá. For this, the case study methodology was used, collecting data through in-depth interviews, finding that fear is the most frequent affectation for victims of physical violence; the indisposition to day activities for victims of psychological violence; physiological reactivation for victims of sexual violence and dependency for victims of economic violence